The C-Domain of Oleuropein β-Glucosidase Assists in Protein Folding and Sequesters the Enzyme in Nucleus. Issue 3 (8th May 2017) - Koudounas, Konstantinos; Thomopoulou, Margarita; Michaelidis, Christos; Zevgiti, Efstathia; Papakostas, Georgios; Tserou, Paraskevi; Daras, Gerasimos; Hatzopoulos, Polydefkis
Abstract : The C terminus of the oleuropein - specific β - glucosidase from olive encompasses a bifunctional role to assemble an active multimeric enzyme and to regulate nuclear localization, keeping it conditionally inaccessible. Abstract: Oleuropein, a terpene-derived glycosylated secoiridoid biosynthesized exclusively by members of the Oleaceae family, is involved in a two-component defense system comprising a β-glucosidase that activates oleuropein into a toxic glutaraldehyde-like structure. Oleuropein and its deglycosylated derivatives have high pharmaceutical interest. In this study we determined that the in planta heterologous expressed OeGLU, an oleuropein-specific β-glucosidase from olive ( Olea europaea ), had enzymatic kinetics similar to the olive native enzyme. The C terminus encompassing the nuclear localization signal sequesters the enzyme in the nucleus, and predetermines the protein-protein recognition and homodimerization. Biochemical analysis revealed that OeGLU is a homomultimer with high M r . In silico prediction modeling of the complex structure and bimolecular fluorescence complementation analyses revealed that the C terminus of OeGLU is essential for the proper assembly of an octameric form, a key conformational feature that determines the activity of the enzyme. Our results demonstrate that intrinsic characteristics of the OeGLU ensure separation from oleuropein and keep the dual-partner defensive system conditionally inactive. Upon cell destruction, the dual-partner defense system is activated and olive massively releases the arsenal of defense.